Serendipita indica Promotes the Growth of Tartary Buckwheat by Stimulating Hormone Synthesis, Metabolite Production, and Increasing Systemic Resistance - Meijia Zheng; Shanpu Zhong; Wenjing Wang; Zizhong Tang; Tongliang Bu; Qingfeng Li (Journal of Fungi, 2023)
The main objective of this study was to investigate the influence of Serendipita indica on the growth of Tartary buckwheat plants. This study highlighted that the roots of Tartary buckwheat can be colonized by S. indica and that this fungal endophyte improved plants height, fresh weight, dry weight, and grain yield. In the meantime, the colonization of S. indica in Tartary buckwheat leaves resulted in elevated levels of photosynthesis, plant hormone content, antioxidant enzyme activity, proline content, chlorophyll content, soluble sugars, and protein content. Additionally, the introduction of S. indica to Tartary buckwheat roots led to a substantial rise in the levels of flavonoids and phenols found in the leaves and seeds of Tartary buckwheat. In addition, S. indica colonization reduced the content of malondialdehyde and hydrogen peroxide when compared to non-colonized plants. Importantly, the drought tolerance of Tartary buckwheat plants is increased, which benefits from physiology and bio-chemical changes in plants after S. indica colonized. In conclusion, we have shown that S. indica can improve systematic resistance and promote the growth of Tartary buckwheat by enhancing the photosynthetic capacity of Tartary buckwheat, inducing the production of IAA, increasing the content of secondary metabolites such as total phenols and total flavonoids, and improving the antioxidant enzyme activity of the plant.